(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
India is known as ancient Guru Worlds. In our society, all teachers have a reputation. By midday or until the beginning of modern times, we can say more or less the same situation. With time changes, teachers face many internal and external problems. Primary education is the foundation of education and, compared with primary schools, primary schools are very close to the community. Community participation in the administration of primary school is therefore more important. The head teacher of primary school takes care of numerous other responsibilities. The present generation of learners is one of the most important concerns of educators around the world, and particularly in India. As a nation with about 28 million youth, India is relatively young each year. Over 50% of the population is under 25 years of age, and over 65% are under 35 years of age. By 2020, an Indian average age is expected to be 29years, whereas China is expected to be 37years and Japan to be 48years. The high youth population in India, however, will not help the economy unless universal education throughout India is achieved. India is currently faced with the major problem of improving the quality of urban education through all pedagogical innovations, while rural students and their education continue to be largely ignored. Education deserves a much better look, particularly when the problem is so many - the attitude of teachers, the absence of teachers and the poor quality of teachers - with 65% of the population living in rural India. Since we know the scenario of rural schools, we need to reflect on these principles that we can transfer from our practice to other people. We should concentrate on the main problems of head teachers and make some good suggestions. Theoretics, principles and practices, pedagogy not applications in the education system need to be established in research not evaluation. Only head teachers can change the school environment in a sustainable way.